Bacteriological studies of liver parenchyma in controls and in patients with gallstones or common bile duct stones with or without acute cholangitis - Csendes, A; Hurdiles, P; Diaz, J C; Maluenda, F; Ferrario, M; Compan, A (Hepato-gastroenterology, 1995)
The presence of aerobic and/or anaerobic bacteria in the liver parenchyma, gallbladder bile, and common bile duct was investigated. There were 15 control subjects, 32 cases with symptomatic gallstones, 16 patients with common bile duct stones without acute cholangitis and 8 cases with common bile duct stones with an acute suppurative cholangitis. No bacteria were isolated in controls. The percentage of positive cultures in liver parenchyma increased in proportion to the severity of the biliary tract disease. There was no clear correlation between normal and altered hepatic histology and the presence or absence of bacteria except in patients with acute cholangitis. When biliary tract obstruction is present, the biliary tract is more vulnerable to invasion of bacteria and therefore increases the chance of spread into the liver parenchyma.